Weaving Optimal Roles: Mudiroh's Strategy in Optimizing the Role of Musyrifah in Ma'had Aly - Rufaidah Al Islamiyah; Choiriyah, Siti (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2025)
The development of students and teaching in the community are important aspects in the management of education at Ma'had Aly Mohammad Natsir Putri. In this context, the role of mudiroh greatly determines the effectiveness of program implementation, especially in optimizing the role of musyrifah. This study uses a qualitative approach with a case study design, and data collection techniques in the form of interviews, observations, and documentation. Data analysis was carried out through data reduction, data presentation, and drawing conclusions, while data validity was strengthened by source triangulation and member check techniques . The results of the study indicate that mudiroh plays a role in identifying community needs, selecting appropriate musyrifah, and monitoring learning programs. However, limitations in monitoring and emotional readiness of musyrifah are major challenges. Nevertheless, this program has contributed to the development of musyrifah and their readiness to preach. These findings provide insight into the management strategy of the role of educators in preparing them as agents of preaching outside the formal education environment, and highlight the importance of a flexible leadership approach and emotional empowerment for educators.